FAKTOR-FAKTOR PERMINTAAN DAN KESEDIAAN MEMBAYAR WISATAWAN TERHADAP OBJEK WISATA BERDASARKAN TRAVEL COST METHOD - Rosminiati Rosminiati; Sofyan Syahnur; Abubakar Hamzah (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
AbstractThis study aims to determine the factors that influence the number of domestic and foreign tourist visits and to measure the value of willingness to pay for the benefits of tourism objects in Banda Aceh by using the Travel Cost Method Approach. The type of data used is primary and secondary data. Primary data obtained by non-probability sampling, obtained as many as 30 domestic tourists and foreign tourists as many as 30 people, with the method of analysis of ordinary least square (OLS). Secondary data was obtained from the Central Statistics Agency, Tourism Office and other study literature. The results showed that for domestic tourists, the independent variables on travel costs, alternative costs, time costs, and income had significant effect on the number of domestic tourist visits with an R² value of 0.690. In foreign tourists, the independent variables of travel costs, alternative costs, and income have a significant effect on the number of visits, while the cost of time has no effect on the value of R² 0.693. The average value of WTP of foreign tourists is greater than that of domestic tourists, namely domestic tourists with a WTP of 4,000,000 rupiahs while foreign tourists are 217,000,000 rupiah. Given the large contribution of tourism to the economic conditions in Indonesia, especially in Aceh, the government should maintain and pay attention to the conditions of tourism objects and improve tourism facilities so that tourists reach the maximum level of utility so that it will increase the value of PAPs.